Dehydrogenation Catalyst for Organic Hydride on the Basis of Superheated Liquid-Film Concept - Shono, A.; Otake, K.; Kobayashi, D.; Kobayashi, S.; Saito, Y. (Journal of Technology Innovations in Renewable Energy, 2016)
Reversible reaction couples of hydrogenation and dehydrogenation of organic compounds e.g. methylcyclohexane and toluene, or 2-propanol and acetone, are described in terms of hydrogen supplier to fuel cells, which will satisfy our demands of combined heat and power at various compact sizes. Carbon supported nano-sized metal particles, wetted with the liquid substrate in a reactor, was used for conversion of organic hydrides into hydrogen and organic compounds, being separable by distillation. Vigorous nucleate boiling is important for heat transfer as well as for irreversible bubble evolution, leading hydrogen to the vapor phase. Once the bubble is broken at the interface, catalytic hydrogenation will be prohibited, because gaseous hydrogen is unable to dissolve into the boiling liquid. Catalytic dehydrogenation under superheated liquid-film conditions can thus convert low-quality heats into hydrogen energy.